The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jwmg.21670
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and spatiotemporal interactions of a reintroduced mesocarnivore

Abstract: Habitat quality and quantity are key factors in evaluating the potential for success of a wildlife translocation. However, because of the difficulty or cost of evaluating these factors, habitat assessments may not include valuable information on important habitat attributes including the abundance and distribution of prey, predators, and competitors. Fishers (Pekania pennanti) are one of the most commonly reintroduced carnivores in North America, and they are a species of conservation concern in their western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Our findings support their hypotheses, and we add that other factors influencing habitat quality, such as resource availability, should be considered. Other studies have found that low prey densities influenced reintroduction success of mesocarnivores (Moehrenschlager et al, 2004; Jachowski et al, 2011; Scrivner et al, 2016; Parsons et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings support their hypotheses, and we add that other factors influencing habitat quality, such as resource availability, should be considered. Other studies have found that low prey densities influenced reintroduction success of mesocarnivores (Moehrenschlager et al, 2004; Jachowski et al, 2011; Scrivner et al, 2016; Parsons et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Reintroduced American marten Martes americana had low survival rates in the presence of a sympatric carnivore, the fisher Pekania pennanti (Manlick et al, 2017). Another post-reintroduction study found that reintroduced fishers typically selected habitats in conjunction with the relative abundance of their prey, snowshoe hares Lepus americanus (Parsons et al, 2019), and selected marginal habitat in the presence of a sympatric carnivore, the bobcat Lynx rufus . These studies showed that mesocarnivores select habitats based on both prey and predator distributions, and that predictions could be improved if these habitat quality variables are considered when creating habitat suitability models (Parsons et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[53]). Moreover, other putative specialists of old growth—northern flying squirrels ( Glaucomys sabrinus [54]), spotted owls ( Strix occidentalis [55]) and fishers [56,57]—have also been associated with a variety of serial stages as well as heterogeneity. While attributes of old-growth forests are beneficial to meet some life-history needs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This dataset was validated for spatial accuracy by comparing modelled data to observed data from Forest Inventory and Analysis (FIA) plots and comparing accuracy metrics (Riemann & Wilson, 2014).We created separate layers for each forest cover type by summing the basal areas for all representative species within each cell (Figure S1). Basal area is a common measure of tree density used in forestry to represent aboveground biomass (Bettinger et al, 2017) as it contains information on number of trees and size (Balderas Torres & Lovett, 2013), and is often used to represent forest structure in resource selection models (Irwin et al, 2020;Parsons et al, 2019).…”
Section: Predictorsmentioning
confidence: 99%